Psychological distress and associated factors among Palestinian advanced cancer patients: A cross-sectional study - Abu-Odah, Hammoda; Molassiotis, Alex; Zhao, Ivy Y.; Su, Jing Jing; Allsop, Matthew J. (Frontiers in Psychology, 2022)
Objective: There is limited research exploring the experiences of people living with advanced cancer in the Gaza Strip (GS), Palestine. Thus, this study aimed to determine the level of psychological distress, anxiety, and depression among advanced cancer patients in the GS and identify factors associated with a high level of distress. Materials and methods: A secondary analysis was performed using primary data from a larger study focusing on supportive care needs in advanced cancer patients in GS. Three hundred sixty-one patients agreed to participate and filled out the Distress Thermometer (DT) and the Hospital Anxiety and Depression Scale (HADS). Multivariate logistic regression was conducted to identify factors associated with high distress levels. Results: Over two-thirds of advanced cancer patients (70.6%) reported a high level of distress. They also reported a significantly higher distress level than patients with early cancer (96.5% vs. 3.5%; p = .001). About 92.8% of participants reported depression and anxiety symptoms. Physical, emotional, and practical problems were the primary sources of distress. Breast cancer patients were more likely to have psychological distress than colon and stomach cancer patients. Newly diagnosed patients had a higher level of anxiety, depression, and distress than those who had a cancer diagnosis for an extended period. Conclusions: Patients with advanced cancer in the GS exhibited a significantly higher level of psychological distress, depression and anxiety than patients with advanced cancer elsewhere. Efforts should be made to identify psychological distress as a routine part of oncology practice. Future research should further explore the causes of psychological distress in cancer patients in conflict zones and feasible mitigation strategies.